Reliance on Biological Nitrogen Fixation Depletes Soil Phosphorus and Potassium Reserves - Marie Reimer; Tobias Edward Hartmann; Myles Oelofse; Jakob Magid; Else K. Bünemann; Kurt Möller (Nutrient Cycling in Agroecosystems, 2020)
Limited nutrient availability is one of the major challenges in organic farming. Little is known about nutrient budgets of organic farms, the underlying factors or effects on soil fertility. We therefore assessed farm gate nutrient budgets for nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg) and sulfur (S) of 20 organic farms in Germany and analyzed their soil nutri-ent status. In average, the budgets showed a surplus of N (19 kg ha−1), K (5 kg ha−1), S (12 kg ha−1), and Mg (7 kg ha−1), and a deficit of P (−3 kg ha−1). There was, however, high variability between farms (e.g. standard deviation up to ± 36 kg N ha−1), which was mainly explained by different degrees of reliance on biological N fixation (BNF) as N source. When farms obtained more than 60% of their N input through BNF, they had deficits of P (mean −8 kg P ha−1) and K (mean −18 kg K ha−1). Nutrient status of most soils was within the ad-vised corridor, but for P, K and Mg, 10–15% of fields were lower and 45–63% were higher than advised. Extractable soil nutrient contents did not correlate with the nutrient budgets, inputs or outputs. Only extractable soil P increased with increasing P inputs and outputs. Fur-thermore, a decrease in extractable soil P was detected with a prolonged history of organic farming, indicating a risk of soil P mining in organic farming systems. In conclusion, the study revealed nutrient imbalances in organic farming and pointed to P and K scarcity as a major challenge for organic farms with high reliance on BNF in the long term.